1997
DOI: 10.1292/jvms.59.957
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Thymidine Kinase Activity in Dogs with Lymphoma and Leukemia.

Abstract: ABSTRACT. Plasma thymidine kinase (TK) activity was evaluated as a plasma marker for canine lymphoma and leukemia. A tentative "cutoff" value was set at 6.0 U/l as the upper level of plasma TK based on the mean + 2SD of plasma TK activity in 13 clinically healthy dogs. The levels of plasma TK activity in all of the 20 dogs with lymphoma and leukemia were higher than the cut-off value, whereas those in dogs with lymphoma decreased in parallel with the reduction of the tumor mass after chemotherapy. These findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
52
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 13 publications
3
52
0
Order By: Relevance
“…These authors used 6.0 U/L as the upper limit of the reference range for clinically healthy dogs, which is close to the 7.0 U/L reported here. Nakamura et al 10 found that plasma TK was increased in all dogs with ML and leukemia, and thus might be a marker for prediction of tumor proliferation. Furthermore, TK was demonstrated to be a much better tumor marker than serum lactate dehydrogenase (LDH) for evaluation of disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These authors used 6.0 U/L as the upper limit of the reference range for clinically healthy dogs, which is close to the 7.0 U/L reported here. Nakamura et al 10 found that plasma TK was increased in all dogs with ML and leukemia, and thus might be a marker for prediction of tumor proliferation. Furthermore, TK was demonstrated to be a much better tumor marker than serum lactate dehydrogenase (LDH) for evaluation of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,27 Thus, NHL is similar in dogs and humans. In dogs 10 and humans, 28 patients with inflammatory changes and nonneoplastic leukocytosis can have short, transient increases in sTK activity, which returns to normal when the leukocytosis resolves. Hence, a group of 7 dogs with nonneoplastic leukocytosis was included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results published in this issue of the journal offer cautious optimism for sTK as a useful marker of disease activity in dogs with lymphoma, and build on a previous publication on a similar theme. 5 In the data presented in this study, sTK activity correlated with clinical stage of disease at the time of diagnosis, decreased to physiological activity after clinical remission was achieved, and served to portend clinical relapse. Therefore, measurements of sTK might allow recognition of which patients might benefit from early or intensified treatment.…”
mentioning
confidence: 60%
“…The numbers of erythroid progenitors with large, irregular nuclei were increased in peripheral blood. Plasma thymidine kinase activity was high (636 IU/l) compared with clinically healthy control cats (<5 IU/l: n=22) 46 days after the 1st examination, indicating a myeloproliferative condition, as shown in other species [4,5,8]. The cat was regarded as having an MDS-like condition and was treated with low-dose cytarabine (20 mg/m 2 q24h subcutaneously) with reference to treatment for human MDS patients [7,13].…”
mentioning
confidence: 99%